Pembagian Kerja Berdasarkan Gender pada UMKM Berbasis Keluarga di Pasar Leuwiliang, Kota Bogor - Astuti, Riawati; Herawati, Erna (Umbara, 2024)
Small, Micro, and Medium scale Enterprise (SMME) mostly begin in the form of family based business. In this type of business, division of labor is also based on the family division of labor, which is mostly based on the gender division of labor. Drawing from the cases of six SMME in Leuwiliang market at Bogor City, this study aims at analyzing how gender values, norms, and ideology have influenced the gender based division of labor in the family and business of SMME. The study was conducted using a qualitative method with a case study model. Findings of this study suggest that all of the six SMME divide the labor based on gender and that patriarchy has much influence on it. Both husband and wife are involved in the business, but the portion and contribution of each of them are different. Some SMME tend to divide the labor in more patriarchal ways than others. The difference comes from gender values, norms, and ideology believed and practiced by the family. The more patriarchal the family, the more their tendency to divide work based on gender; and the more they give power to men than women. These findings also suggest that in SMME, gender inequality still persists and puts women in the disadvantageous position despite their growing contribution in the family business.